Perancangan Desain Mesin Penyuir Daging Ikan Tongkol Kapasitas 10kg - wadud, ach; Nur Robbi; Mochammad Basjir (RING ME, 2022)
Shredder is the process of tearing or destroying fish evenly and to obtain the desired result. In general, people do the shredding manually which of course takes a very long time, therefore it is necessary to have a solution for making a meat shredding machine that is able to shred quickly and with very good results. The process of shredding fish meat is carried out with a set of rotating knives so that the material to be processed will quickly change its shape from intact to fine shreds. In planning this design using 25 blades, one knife with two blades has a distance of 10 mm to the last blade, and this machine has a capacity of 10 kg with frame dimensions of 65 x 38 x 64 cm, capable of being driven by an electric motor with a power of 2 hp, with a blade shaft rotation of 710 rpm.